Design and Development of an ESP32-Based Battery Monitoring System for Container Cranes with Automatic Transfer Switching (ATS) Mechanism and Telegram Notifications - Lasykar Alim Perdana; Denny Irawan (Jurnal Teknik Elektro dan Komputer TRIAC, 2026)
The development of Internet of Things (IoT) technology has provided convenience in monitoring and controlling industrial systems, including container cranes that utilize batteries as the primary power source. This study aims to design and implement an ESP32-based battery monitoring system equipped with an Automatic Transfer Switch (ATS) mechanism and Telegram notifications. The system utilizes a voltage sensor and an ACS712 current sensor to monitor battery conditions in real time, while relay modules and contactors are employed to perform automatic power source switching when the main battery voltage decreases.The research methodology includes hardware design, software development, IoT system integration, and system performance testing. Voltage sensor testing was conducted using 30 sampling trials and resulted in an average error value of 0.72%, while current sensor testing also used 30 sampling trials and produced an average error value of 1.86%. The ATS system testing demonstrated that the power source switching process was successfully carried out automatically when the main battery voltage reached 11 V. In addition, the ESP32 successfully transmitted real-time Telegram notifications with a response time of approximately 2 seconds during the switching process. Based on the test results, the proposed system is capable of operating stably and effectively, supporting battery monitoring while maintaining power supply continuity.